ANALISIS EKOKRITIK DALAM CERITA RAKYAT SUMATERA UTARA ASAL MULA POHON AREN - Diah Kusyani; Rika Kartika (LUMBUNG AKSARA, 2025)
This study examines the ecological values ​​in the folktale "The Origin of the Sugar Palm Tree" from North Sumatra through an ecocritical approach. This approach highlights the reciprocal relationship between humans and nature as depicted in literary works. The research was conducted using a descriptive qualitative method, using the ecocritical theory of Cheryll Glotfelty and Greg Garrard. The analysis shows that the folktale contains ecological messages in the form of respect for nature, criticism of human greed, and environmental ethical values ​​that are still relevant to the modern context. This story reflects the harmony between humans and nature and serves as an educational medium for instilling ecological awareness in the younger generation.